The important role of soil moisture in controlling autumn phenology of herbaceous plants in the Inner Mongolian steppe. (1st December 2020) - Tao, Zexing; Ge, Quansheng; Wang, Huanjiong; Dai, Junhu
Abstract: Autumn phenology variation in temperate grassland is a direct indicator of land degradation, and a phenology‐based model has been used to simulate human‐induced land degradation. It is important to reveal how environmental factors influence autumn phenology of herbaceous plants. In this study, we examined the effects of temperature, photoperiod, and soil moisture on the leaf withering date (LWD) of four herbaceous species ( Xanthium sibiricum, Plantago asiatica, Iris lactea, and Taraxacum mongolicum ) at 15 sites in the Inner Mongolian steppe from 1981 to 2012. Then, we developed two process‐based models coupling the effects of the three factors based on an existing cold degree–days (CDD)‐based model for predicting the LWD of the four species. The new models showed better accuracy than CDD model during validation. The model structure and parameters suggested that soil moisture likely influenced LWD nonlinearly and presented a multiplicative interaction with temperature and photoperiod. In addition, photoperiod had divergent effects on the accumulation of cold temperature for different species and sites. For X. sibiricum, the photoperiod only determined the start of cold temperature accumulation. Considering the carryover effect of spring phenology did not improve model performance. Our study also showed that local adaptation of plants was commonly ignored when using same parameters in model calibration with observation data from multiple sites; however, model calibrations using site‐specific data were less stable, and the parameters could not be extrapolated across space. It will be necessary to establish a generalized regional model driven by both climatic and genotypic factors in future research.